A power distance in regulating halal food industry? / Sabarina Mohammed Shah and Nor Hafizah Haji Haron - Mohammed Shah, Sabarina; Haron, Nor Hafizah (UiTM Cawangan Johor, 2023)
Issues on halal integrity in the halal food industries have raised concerns amongst the public at large especially Muslims. To safeguard the sanctity of halal integrity, there must be an effective governance mechanism well in place. Currently, there exist several agencies pertaining to halal and Jabatan Kemajuan Islam Malaysia (JAKIM) is perceived to have an ultimatum for they issued the halal certification which is highly recognized worldwide. This study illicit the views from various agencies through qualitative methodology using transcendental phenomenology which views consciousness as the center for transcending intention and explicit behaviours. Questions formulated are to capture their specific experience which has been approved by the Ethics Committee for Research Involving Human Subjects (Malay acronym, JKEUPM). A focus group discussion was carried out with the officers from these agencies. The findings revealed that there exists an unclear jurisdiction line ofpower amongst the agencies, a low level of accountability amongst C suites, and a high level ofpower distance in regulating the halalfood industry. Keywords: Accountability, Focus Group Discussion, Halal Food Industry, Hofstede Power Distance, Governance, Phenomenological Approach